Ehrgeizige Pläne der Ampelkoalition zur beruflichen Weiterbildung; Ambitious plans of the "traffic light" coalition for further vocational training - Hartmut Seifert (Wirtschaftsdienst, 2022)
Der Koalitionsvertrag der neuen Ampelregierung listet zwar Vorschläge zur Neuausrichtung der beruflichen Weiterbildung auf, bleibt aber mit seinen Vorschlägen unkonkret. Der vorliegende Beitrag erläutert die im Koalitionsvertrag genannten Weiterbildungskonzepte und zeigt auf, wie sie sinnvoll miteinander verknüpft werden könnten, um die berufliche Weiterbildung zu fördern und Engpässen auf dem Arbeitsmarkt in Zukunft entgegenzuwirken. – – The article presents the proposals for the reorientation of vocational training listed in the coalition agreement of the new "traffic light" government and discusses them against the background of the upcoming challenges of ecological and digital structural change. However, the proposals are unrelated and do not always indicate whether they are intended to replace, supplement or expand existing programmes and approaches. For this reason, a coherent conception cannot be identified. The article shows how a sustainable concept can be formed from the approaches that are still unconnected.
Keywords: J21; J68; 330